Functional Supramolecular Polymers for Biomedical Applications. (12th November 2014) - Dong, Ruijiao; Zhou, Yongfeng; Huang, Xiaohua; Zhu, Xinyuan; Lu, Yunfeng; Shen, Jian
<x xml:space="preserve">Abstract</x> As a novel class of dynamic and non‐covalent polymers, supramolecular polymers not only display specific structural and physicochemical properties, but also have the ability to undergo reversible changes of structure, shape, and function in response to diverse external stimuli, making them promising candidates for widespread applications ranging from academic research to industrial fields. By an elegant combination of dynamic/reversible structures with exceptional functions, functional supramolecular polymers are attracting increasing attention in various fields. In particular, functional supramolecular polymers offer several unique advantages, including inherent degradable polymer backbones, smart responsiveness to various biological stimuli, and the ease for the incorporation of multiple biofunctionalities (e.g., targeting and bioactivity), thereby showing great potential for a wide range of applications in the biomedical field. In this Review, the trends and representative achievements in the design and synthesis of supramolecular polymers with specific functions are summarized, as well as their wide‐ranging biomedical applications such as drug delivery, gene transfection, protein delivery, bioimaging and diagnosis, tissue engineering, and biomimetic chemistry. These achievements further inspire persistent efforts in an emerging interdisciplinary research area of supramolecular chemistry, polymer science, material science, biomedical engineering, and nanotechnology.